1994
DOI: 10.1021/j100066a020
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of the Reaction of Trimethylsilane with O(3P) Atoms

Abstract: The reaction O(,PJ) + (CH&SiH -products (1) has been investigated by the discharge/fast-flow method with mass spectrometric detection (DF-MS) over 298-773 K and by the flash photolysis/resonance fluorescence (FP-RF) technique over 293-549 K. The rate constants from both methods are in close accord and may be summarized by kl(T) = 5.6 X lo-" exp(-1005 K/7') cm3 molecule-' s-l for 290-770 K. There is reasonable agreement with previous room-temperature studies. kl is larger than k2 for 0 + SiH4 (2), similar to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…A similar paradox and a possible interpretation in frontier orbital terms was presented earlier for the reactions of silanes with O( 3 P) atoms [16]. In that case it was argued that as the degree of methylation increases, electron withdrawal by the methyl groups makes the Si atom more positive.…”
Section: Reactivity Trends and Likely Productssupporting
confidence: 59%
“…A similar paradox and a possible interpretation in frontier orbital terms was presented earlier for the reactions of silanes with O( 3 P) atoms [16]. In that case it was argued that as the degree of methylation increases, electron withdrawal by the methyl groups makes the Si atom more positive.…”
Section: Reactivity Trends and Likely Productssupporting
confidence: 59%
“…The oxygen atoms are consumed by the reaction with silanes, as well as the wall of reaction tube by the collision, as given in equations (5) and (6) (6) where, k bi is the rate constant of bimolecular reaction; k w is the first order rate constant for wall effect regarding the consumption due to O 2 and also reaction products. Near the injection point, the rate equation for the consumption of oxygen atom is described by the equation (I) since the reaction (5) where, represents the concentration of remaining O( 3 P) when the samples are completely consumed.…”
Section: Resultsmentioning
confidence: 99%
“…Buchta et al reported the experimental work on the reaction of O( 3 P) with silanes by discharge flow method and mass spectrometry. 5,6 The rate constant for the reaction of O( /RT] in the range of 298-773 K, however, the rate expression considered only hydrogen abstraction channel rather than total reaction pathways. 5 In this note, we report kinetic data on the measurements of total reaction pathways for reaction of O( …”
mentioning
confidence: 99%
“…The gasphase reactions of alkylsilanes with various atoms and free radicals have been the active subject of many studies for a long time. [1][2][3][4][5][6][7][8][9][10][11][12][13] In this paper we present a theoretical study on the reaction of atomic H with monoethylsilane EtSiH 3 . The reasons for initiating such a work are 3-fold.…”
Section: Introductionmentioning
confidence: 99%
“…Alkylsilanes are common precursors used in chemical vapor deposition (CVD) to produce semiconductor devices. The gas-phase reactions of alkylsilanes with various atoms and free radicals have been the active subject of many studies for a long time. In this paper we present a theoretical study on the reaction of atomic H with monoethylsilane EtSiH 3 . The reasons for initiating such a work are 3-fold.…”
Section: Introductionmentioning
confidence: 99%